2021
DOI: 10.7150/ijbs.58026
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the effects of PYCR1 on cell function and its associated mechanism in hepatocellular carcinoma

Abstract: Overexpression of pyrroline-5-carboxylate reductase 1 (PYCR1) has been associated with the development of certain cancers; however, no studies have specifically examined the role of PYCR1 in hepatocellular carcinoma (HCC). Based on The Cancer Genome Atlas expression array and meta-analysis conducted using the Gene Expression Omnibus database, we determined that PYCR1 was upregulated in HCC compared to adjacent nontumor tissues (P < 0.05). These data were verified using quantitative real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…According to the established search strategy, 89 literatures were initially screened. After exclusion according to the literature screening flow chart (Figure 1), eight clinical research literatures were finally included, and the studied population consisted of 728 cases (9)(10)(11)(12)(13)(14)(15)(16). The literature was of high quality and without significant publication bias.…”
Section: Literature Screening Resultsmentioning
confidence: 99%
“…According to the established search strategy, 89 literatures were initially screened. After exclusion according to the literature screening flow chart (Figure 1), eight clinical research literatures were finally included, and the studied population consisted of 728 cases (9)(10)(11)(12)(13)(14)(15)(16). The literature was of high quality and without significant publication bias.…”
Section: Literature Screening Resultsmentioning
confidence: 99%
“… 24 Additionally, small molecule inhibitors of PYCR1 have been shown to impair the spheroidal growth of MCF10A H-RAS V12 breast cancer cells 25 and proliferation of myelogenous erythroleukemic K562 and epithelial breast cancer MDA-MB-231 cell lines. 26 Recent therapeutic studies have shown that silencing of PYCR1 reduces the progression and proliferation of the cancer cells 27 , 28 and leads to the induction of apoptosis. 11 Increased apoptosis with loss of PYCR1 has also been reported in other diseases such as autosomal recessive cutis laxa.…”
Section: Discussionmentioning
confidence: 99%
“…One research group based on bioinformatics technology, reported that the PYCR1 was overexpressed in HCC cells. It played a multifaceted regulatory assignment in various biological pathways, such as cell communication, cell growth, cell migration, mitogen-activated protein kinase cascade, etc [ 33 ]. Another group observed that PYCR1 gene silencing could inhibit the proliferation of hepatoma cells, promote apoptosis, and significantly inhibit the volume and size of transplanted tumors in nude mice by regulating the JNK/IRS1 pathway [ 10 ].…”
Section: Discussionmentioning
confidence: 99%